PENINGKATAN KEBERDAYAAN DAN EKONOMI LOKAL MASYARAKAT PESISIR MELALUI DIVERSIFIKASI OLAHAN PRODUK RUMPUT LAUT DI DESA LAMBAKARA - Krisman Henggu (Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
Seaweed processing in the coastal community of Lambakara Village, located in the Pahunga Lodu District, mainly focuses on producing dried seaweed, which serves as a raw material for chips. However, one significant challenge these communities face is the rejection of dried seaweed by companies due to physical defects and inadequate drying. As a result, much of the rejected seaweed remains unused, leading to both economic and environmental inefficiencies. To address this issue, initiatives for technology transfer are essential to enhance the community's knowledge and skills in diversifying seaweed into value-added food products, such as brownies and bread. Training and mentoring activities, conducted using the Participatory Rural Appraisal (PRA) approach, have emphasized inclusive and community-driven Development. Evaluation results show a notable increase in community empowerment following these training and mentoring sessions. This is evident in the community's ability to independently create seaweed-based brownies and bread, as well as their proficiency in conducting business analysis and feasibility assessments on their own. To ensure the sustainability of community empowerment in Lambakara Village, a collaborative partnership model involving academia, business, and government (ABG) has been proposed. This partnership aims to position the coastal community as a hub for science and technology transfer, thereby contributing to economic improvement and poverty alleviation.